Invasive Salmonella exploits divergent immune evasion strategies in infected and bystander dendritic cell subsets. Issue 1 (December 2018) - Aulicino, Anna; Rue-Albrecht, Kevin; Preciado-Llanes, Lorena; Napolitani, Giorgio; Ashley, Neil; Cribbs, Adam; Koth, Jana; Lagerholm, B.; Ambrose, Tim; Gordon, Melita; Sims, David; Simmons, Alison
Abstract Non-typhoidalSalmonella (NTS) are highly prevalent food-borne pathogens. Recently, a highly invasive, multi-drug resistantS . Typhimurium, ST313, emerged as a major cause of bacteraemia in children and immunosuppressed adults, however the pathogenic mechanisms remain unclear. Here, we utilize invasive and non-invasiveSalmonella strains combined with single-cell RNA-sequencing to study the transcriptome of individual infected and bystander monocyte-derived dendritic cells (MoDCs) implicated in disseminating invasive ST313. Compared with non-invasiveSalmonella, ST313 directs a highly heterogeneous innate immune response. Bystander MoDCs exhibit a hyper-activated profile potentially diverting adaptive immunity away from infected cells. MoDCs harbouring invasiveSalmonella display higher expression ofIL10 andMARCH1 concomitant with lower expression ofCD83 to evade adaptive immune detection. Finally, we demonstrate how these mechanisms conjointly restrain MoDC-mediated activation ofSalmonella -specific CD4+ T cell clones. Here, we show how invasive ST313 exploits discrete evasion strategies within infected and bystander MoDCs to mediate its dissemination in vivo. Salmonella employ a range of strategies to counter host defences during infection. Here, Aulicino et al. use single-cell RNA-sequencing to examine the effects of invasive and non-invasive strains of Salmonella, revealing discrete and divergent immune evasion strategies in infected and bystander dendritic cells.